1976
DOI: 10.1073/pnas.73.5.1542
|View full text |Cite
|
Sign up to set email alerts
|

Ability of insulin to increase calcium binding by adipocyte plasma membranes.

Abstract: Calcium specifically binds to adipocyte plasma membranes, demonstrating two classes of binding sites having affinity constants of 4.5 X 104 M-and 2.0 X 1O0 M-'. Insulin (100 microunits/ml) added directly to the isolated plasma membranes caused no alteration in calcium binding, whereas incubation of the adipocytes with 100 microunits/m of insulin resulted in a 25.0 k 1.6% increase in calcium binding to the subsequently isolated plasma membranes. The increase in calcium binding produced by insulin resulted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…However, in the present study we failed to detect any change in the calcium accumulating abilities of heart sarcolemma, microsomes and mitochondria. It should be mentioned that some investigators (McDonald, Burns & Jarett, 1976) have shown a stimulatory effect of insulin on the nonspecific calcium binding by adipocyte plasma membranes while others have reported a depressant action by employing liver plasma membranes. Whether this discrepancy is due to tissue specificity or some other reason is not clear at this time.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study we failed to detect any change in the calcium accumulating abilities of heart sarcolemma, microsomes and mitochondria. It should be mentioned that some investigators (McDonald, Burns & Jarett, 1976) have shown a stimulatory effect of insulin on the nonspecific calcium binding by adipocyte plasma membranes while others have reported a depressant action by employing liver plasma membranes. Whether this discrepancy is due to tissue specificity or some other reason is not clear at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive (31). With respect to the inhibitory effect of calcium, it is well known that plasma membranes have specific binding sites for calcium (32)(33)(34) and that calcium increases the binding of particular ligands to the plasma membranes of several tissues (35,36), but it is not known whether the binding of calcium initiates the latter responses.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes were isolated from rat epididymal fat pads as described (11) and plasma membranes were prepared as described by McKeel (12,13). The plasma membrane fractions were routinely frozen in dry ice/ethanol, stored at -70'C, and used within 1 week after preparation.…”
Section: Methodsmentioning
confidence: 99%